Deans Participate in BASIC Workshop in Addis Ababa, September 06 - 09, 2004 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
The workshop on Building Africa´s Science and Institutional Capacity (BASIC) was convened by the Forum for Agricultural Research in Africa (FARA), hosted by the Commission of the African Union and made possible by funding from the government of Norw